Analysis of American Exceptionalism and Cultural Imperialism through Starvin’ Marvin in Space Series - Puspita, Gita Zhahra; Prihatika, Yusrina Dinar (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyses how South Park represents American Exceptionalism and Cultural Imperialism in the episode Starvin’ Marvin in Space. The research focuses on how Western superiority and moral beliefs are expressed through religion, language, politic, and culture. Using John Winthrop’s City upon a Hill and Edward Said’s Orientalism as main theories, this study explains how America defines itself as a chosen and civilized nation, while Africa is shown as “the Other,” poor and uneducated. The qualitative descriptive method is used to analyse selected scenes through visuals, dialogues, and character actions. The findings reveal that Sister Hollis’s religious mission reflects moral superiority and missionary control, while scenes of African poverty reproduce Western stereotypes through satire. The episode also presents American authority through CIA’s domination, representing political power under moral disguise. This study concludes that the episode continues colonial ideas and exceptionalist values in modern media satire.